PSEN1 Mutant iPSC-Derived Model Reveals Severe Astrocyte Pathology in Alzheimer's Disease - Oksanen M (CELL PRESS, 2022)
Alzheimer's disease (AD) is a common neurodegenerative disorder and the leading cause of cognitive impairment. Due to insufficient understanding of the disease mechanisms, there are no efficient therapies for AD. Most studies have focused on neuronal cells, but astrocytes have also been suggested to contribute to AD pathology. We describe here the generation of functional astrocytes from induced pluripotent stem cells (iPSCs) derived from AD patients with PSEN1 Delta E9 mutation, as well as healthy and gene-corrected isogenic controls. AD astrocytes manifest hallmarks of disease pathology, including increased beta-amyloid production, altered cytokine release, and dysregulated Ca2+ homeostasis. Furthermore, due to altered metabolism, AD astrocytes show increased oxidative stress and reduced lactate secretion, as well as compromised neuronal supportive function, as evidenced by altering Ca2+ transients in healthy neurons. Our results reveal an important role for astrocytes in AD pathology and highlight the strength of iPSC-derived models for brain diseases.